DISCOUNT FACTOR, FUTURE FLOWS AND DETERIORATION OF TANGIBLE AND INTANGIBLE ASSETS - Arrarte Mera, Raúl Alberto (2016)
This work is an exploratory-descriptive-quantitative analysis; a mathematical simulation of an increasing and decreasing flow of future income at low and high interest rates; to deduce their results. Goals: A) To evaluate a fair and reasonable discount factor to calculate the projection of future flows of tangible and intangible fixed assets. B) To verify a way to estimate the recoverable value of a Cash-Generating Unit (CGU). C) To study the extent to which a global interest rate is appropriate to fight against money laundering and corruption. We conclude: if we apply a high interest rate we affect the company with less profits and the State with lower tax revenues. If the rate is low, the opposite is true. We confirm that it is convenient for our countries to make quarterly normalization of interest rates at the global level by the IASB.